Nature inspired singlet oxygen generation to access α-amino carbonyl compounds via 1, 2-acyl migration. Issue 1 (15th December 2020) - Schilling, Waldemar; Zhang, Yu; Sahoo, Prakash Kumar; Sarkar, Samir Kumar; Gandhi, Sivaraman; Roesky, Herbert W.; Das, Shoubhik
Abstract : We have discovered chlorophyll catalyzed 1, 2-acyl migration reactions to achieve α-amino carbonyl compounds directly from the enaminones. Abstract : We have discovered chlorophyll catalyzed 1, 2-acyl migration reactions to achieve α-amino carbonyl compounds directly from the enaminones. In general, singlet oxygen is generated during photosynthesis in the photosystem II center. This singlet oxygen can readily react with the unsaturated double bonds present in biomolecules. This reactivity intrigued us to apply this concept towards unsaturated enaminones and others to achieve highly valuable compounds. Indeed, this photosensitizer is very cheap, commercially available, main group metal based and provided excellent efficiency for singlet oxygen mediated chemistry by achieving high turnover number (TON) > 300 with a high turnover frequency (TOF) of 50 h −1 . Finally, a combination of DFT calculations and detailed mechanistic experiments provided the exact role of the photosensitizer and clear insights into the reaction.